2023
DOI: 10.3390/medicina59010167
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Level in Synovial Fluid—Association with Joint Destruction in Early Rheumatoid Arthritis

Abstract: Background and objective: Matrix metalloproteinases (MMPs) are the key enzymes in the pathogenesis of cartilage and joint damage and potentially a new biomarker of the early erosive form of rheumatoid arthritis (RA). Firstly, the study aimed to compare the level of MMP-9 in plasma (PL) and synovial fluid (SF) of patients with RA and osteoarthritis (OA). Secondly, the goal was to examine the association of MMP-9 level in PL and SF with early erosive changes in RA, and finally, to determine the association of MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Примером таких лекарственных препаратов, внедренных в клиническую практику, являются ингибиторы янус-киназ: тофацитиниб, пефицитиниб и упадацитиниб [20]. В тоже время препараты на основе малых молекул могут воздействовать на иные биомишени, которые опосредуют формирование патогенеза РА, например ММП [21].…”
Section: влияние анализируемых соединений и референта на изменение ко...unclassified
“…Примером таких лекарственных препаратов, внедренных в клиническую практику, являются ингибиторы янус-киназ: тофацитиниб, пефицитиниб и упадацитиниб [20]. В тоже время препараты на основе малых молекул могут воздействовать на иные биомишени, которые опосредуют формирование патогенеза РА, например ММП [21].…”
Section: влияние анализируемых соединений и референта на изменение ко...unclassified
“…Specific MP patterns can even predict that some patient populations may have a greater risk for certain complications compared to others, suggesting tailored follow-up programs. There is evidence of these applications with several diseases, such as cardiovascular disease (e.g., atrial fibrillation, aneurysms, chronic venous disease, venous thromboembolism, vascular ulcers), cancer (i.e., lung carcinoma, ovarian cancer), inflammatory diseases (i.e., rheumatoid arthritis), oral diseases (i.e., periodontal disease), proctologic diseases (i.e., hemorrhoids), infective diseases (i.e., COVID-19), and neurodegenerative diseases (i.e., Alzheimer's disease) [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Metalloproteinases As Biomarkersmentioning
confidence: 99%
“…A different study identified a significant correlation between ACPA and MMP-9 levels in synovial fluid compared to RF and MMP-9 level [ 88 ]. This highlighted the importance of the ACPA parameter over RF for diagnosis of early RA.…”
Section: Other Matrix Metalloproteinases-related Developments In Oste...mentioning
confidence: 99%